2022
DOI: 10.3390/ijerph191610197
|View full text |Cite
|
Sign up to set email alerts
|

Does Cleaner Household Energy Promote Agricultural Green Production? Evidence from China

Abstract: Cleaner household energy for agricultural green production can significantly alleviate energy poverty and food security, thus contributing to global sustainable development. Using survey micro-data collected from Sichuan Province, the ordered probit model, OLS model, and instrumental variables approach were applied for empirical analysis. The results show that: (1) cleaner household energy significantly enhances farmer’s agricultural green production awareness and improves agricultural green production levels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The goal of clean production is to minimize the environmental impact of agricultural activities while maximizing resource efficiency and sustainability. Adopting clean production practices can reduce pollution, protect biodiversity, and safeguard human health [86]. Clean agricultural production involves two aspects: reducing the use of chemical inputs and improving the efficiency of energy resources.…”
Section: Entropy Methods and Weighted Topsis Methodsmentioning
confidence: 99%
“…The goal of clean production is to minimize the environmental impact of agricultural activities while maximizing resource efficiency and sustainability. Adopting clean production practices can reduce pollution, protect biodiversity, and safeguard human health [86]. Clean agricultural production involves two aspects: reducing the use of chemical inputs and improving the efficiency of energy resources.…”
Section: Entropy Methods and Weighted Topsis Methodsmentioning
confidence: 99%
“…The contribution of the study is also important due to the lack of knowledge about the nature of SD, as was found out [ 111 ], and because different actions that have a positive impact on today’s world become an inevitable trend in the SD era [ 112 ]. Sustainable solutions play a significant role [ 113 ] in contributing to global SD [ 114 ] and must be supported also by theoretical contribution represented by the newly developed model in this study. Recently, the world economy has faced many unexpected situations, e.g., economic crisis, economic expansion, and special situations such as natural disasters or pandemics (e.g., the COVID-19 pandemic) and new models explaining how to make supply chains more resilient and flexible as well as efficient and sustainable are understudied.…”
Section: Discussionmentioning
confidence: 93%
“…Access to clean technologies can significantly impact food production by reducing environmental damage and waste while increasing resource efficiency in the food-production processes. Bhandari, 2018;Gorjian et al, 2022;Li et al, 2022;Nwachukwu, 2023;Sargentis et al, 2021;Zhang et al, 2022). This technology can help to make the cleaning process more efficient, resulting in cost savings in the production process.…”
Section: Linkages Between Green Technologies and Food Productionmentioning
confidence: 99%
“…Hence, enhanced access to clean cooking technologies can potentially improve food safety and quality, meeting the stringent standards of export markets. Some studies have discussed the potential of renewable energy integration in agriculture, including cooking, as a means to promote sustainable food production and enhance export competitiveness (Aganbegyan et al, 2020; Bhandari, 2018; Gorjian et al, 2022; Li et al, 2022; Nwachukwu, 2023; Sargentis et al, 2021; Zhang et al, 2022). This technology can help to make the cleaning process more efficient, resulting in cost savings in the production process.…”
Section: Literature Reviewmentioning
confidence: 99%